Analysis of The Impact of Locus of Control and Academic Procrastination on Student Learning Achievement - Rohman, Moh. Aziz; Susanto, Rudi (Jurnal Riset dan Inovasi Pembelajaran, 2024)
Students must have high discipline, creativity, and work ethic when dealing with their tasks to become quality resources. However, some aspects that impact student performance include locus of control and academic proxination. Therefore, this study aims to assess the extent of the impact of Locus of Control and Academic Procrastination on Student Learning Achievement. We used an analytic survey with a cross-sectional design. The study population was first-year students of the Nautical Study Program at Makassar Polytechnic of Shipping Science. The sampling technique used simple random sampling with a sample of 92 students. Data collection tools using questionnaires and tests. Data analysis techniques using multiple linear regression. The results showed that locus of control and academic procrastination significantly influence student achievement. In this case, locus of control has a positive relationship with student achievement, which means that the better the locus of control of students, the better student achievement. Academic procrastination has a negative relationship with student learning achievement; the higher the academic procrastination, the lower the student's learning achievement.